Power fluid current calculation in hydrounits channel with operational wave resistance usage - Кулініч, Сергій Павлович (Eastern-European Journal of Enterprise Technologies, 2012)
The design procedure of factors of transfer of pipelines, channels and chambers of volumetric hydrounits is resulted. Legitimacy of its application is proved